2008
DOI: 10.1007/s10705-008-9240-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of reduced tillage agriculture on carbon dynamics in silt loam soils

Abstract: Reduced tillage (RT) agriculture is an effective measure to reduce soil loss from soils susceptible to erosion in the short-term and is claimed to increase the soil organic carbon (SOC) stock. The change in distribution and total SOC stock in the 0-60 cm layer, the stratification of microbial biomass carbon (MB-C) content in the 0-40 cm layer and the carbon (C) mineralization in the upper 0-5 cm layer in silt loam soils in Western Europe with different periods of RT agriculture were evaluated. Ten fields at se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Interestingly, data given in Johnson et al (2005) and Franzluebbers (2005) are reduced to 4.7 and 2.9 Mg C ha -1 , respectively, when only studies giving data for this depth are considered. This illustrates the importance of considering at least the entire tilled depth in this type of studies, as recently demonstrated by Eriksen-Hamel (2008) andD'Haene et al (2009). Studies providing data beyond this depth could be of great value in this sense, and are scarce in the literature.…”
Section: Discussionmentioning
confidence: 80%
“…Interestingly, data given in Johnson et al (2005) and Franzluebbers (2005) are reduced to 4.7 and 2.9 Mg C ha -1 , respectively, when only studies giving data for this depth are considered. This illustrates the importance of considering at least the entire tilled depth in this type of studies, as recently demonstrated by Eriksen-Hamel (2008) andD'Haene et al (2009). Studies providing data beyond this depth could be of great value in this sense, and are scarce in the literature.…”
Section: Discussionmentioning
confidence: 80%
“…The SOC under MT × S wrm was statistically different from all other treatment combinations. Baker et al [30] and D' haene et al [31] showed that more SOC under MT or no tillage in comparison to extensive tillage. Naresh et al [32] reported that the combination of reduced tillage with crop residue retention increases the SOC in the top soil.…”
Section: Effects Of Tillage Practices and Crop Residue Retention On Smentioning
confidence: 99%
“…The C mineralization experiment was started from undisturbed soil samples, because the crucial difference between soils under CT and ZT lies in the differences in soil structure. An incubation experiment with disturbed soils only would thus eliminate the inherent difference in soil quality between both systems (D'Haene et al 2009). The samples for C mineralization were collected in triplicates using stainless steel rings so that undisturbed samples were obtained.…”
Section: Soil Samplingmentioning
confidence: 99%